Doxorubicin-loaded PEGylated liposome modified with ANGPT2-specific peptide for integrative glioma-targeted imaging and therapy - Hongyan Li; Rong Gan; Jiadi Liu; Duling Xu; Qiyue Zhang; Haidong Tian; Huijun Guo; Haijun Wang; Zhimin Wang; Xianwu Zeng (Materials Today Bio)
Liposomal nanocarriers are able to carry peptides for efficient and selective delivery of radioactive tracer and drugs into the tumors. Angiopoietin 2 (ANGPT2) is an excellent biomarker for precise diagnosis and therapy of glioma. The present study aimed to design ANGPT2-specific peptides to modify the surface of nanoliposomes containing doxorubicin (Dox) for integrative imaging and targeting therapy of glioma. The targeted ANGPT2 peptides were designed using the molecular operating environment. Peptide-conjugated PEGlated liposomes containing Dox (peptide-Lipo@Dox) were prepared for radionuclide and drug delivery. Glioma cell functions were determined based on cell cycle and viability, apoptosis, cell invasion and migration, and colony-formation assays. The anti-tumor effect of peptide-Lipo@Dox was validated in intracranial U87-MG cell glioma-bearing mice in vivo. The peptides GSFIHSVPRH (GSF) and HSVPRHEV (HSV) showed specific affinity for ANGPT2 and a better cellular uptake in U87-MG cells. Micro-positron emission tomography (PET)/computed tomography (CT) imaging was used to visualize the orthotopic transplantation of glioma in the brain 1 h after injection of radionuclide 68Ga-labeled peptide-Lipo@Dox. Lipo@Dox with peptide modification demonstrated stable Dox loading, small sizes (<40 nm), and enrichment in the tumor region of the mouse brain. Peptide-Lipo@Dox treatment inhibited the Tie-2/Akt/Foxo-1 pathway, thereby inhibiting cell invasion and migration, cell viability, and colony-forming ability of U87-MG cells. Lipo@Dox peptide modification showed a better suppression of glioma development than Lipo@Dox. Thus, the ANGPT2-specific peptides were successfully designed, and the PEGylated liposome modified with ANGPT2-specific peptide served as part of a potent delivery method for integrative glioma-targeted imaging and therapy.